Response to three component seismic motion of arbitrary direction. - Hernandez, Julio H.
This paper presents a response spectrum analysis procedure for the calculation of the maximum structural response to three translational seismic components that may act at any inclination relative to the reference axes of the structure. The formula GCQC3, a generalization of the known CQC3-rule, incorporates the correlation between the seismic components along the axes of the structure and the intensity disparities between them. Contrary to the CQC3 rule where a principal seismic component must be vertical, in the GCQC3 rule all components can have any direction. Besides, the GCQC3 rule is applicable if we impose restrictions to the maximum inclination and/or intensity of a principal seismic component; in this case two components may be quasi horizontal and the third may be quasi vertical. This paper demonstrates that the critical responses of the structure, defined as the maximum and minimum responses considering all possible directions of incidence of one seismic component, are given by the square root of the maximum and minimum eigenvalues of the response matrix R, of order 3 x 3, defined in this paper; the elements of R are established on the basis of the modal responses used in the well known CQC rule. The critical responses to the three principal seismic components with arbitrary directions in space are easily calculated by combining the eigenvalues of R and the intensities of those components. The ratio rmax/rsrss between the maximum response and the srss response, the latter being the most unfavourable response to the principal seismic components acting along the axes of the structure, is bounded between 1 and 3y2a/(y2a+y2b+y2c), where ya>yb>yc are the relative intensities of the three seismic components with identical spectral shape.
Keywords: Seismic components; Response spectrum analysis; Multicomponent earthquake; CQC3.; GCQ3.; Critical response